2016
DOI: 10.1590/1518-8345.1242.2788
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' experiences working with nursing students in a hospital: a phenomenological enquiry

Abstract: Objective: this paper explores the experiences of registered nurses working with Spanish nursing students within the hospital. Methods: a qualitative phenomenological approach was followed. Purposeful sampling was employed. Twenty-one registered nurses, from a public hospital located in Spain, were included in the study. Data were collected by means of unstructured and semi-structured interviews and were analysed using Giorgi's proposal. The Consolidated Criteria for Reporting Qualitative Research were followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
4
22
0
5
Order By: Relevance
“…Likewise, the overvaluation of one over the other ends up compromising the education in line with the social changes (16) . It is believed, therefore, that this contextualized articulation between teaching and service facilitates learning and leads the student to a reflective practice based on a realistic experience in the different environments of the health services (17)(18) . As far as Professor Mary Anne Small is concerned, her former students presented some features that made it possible to project the image of a tall, wide-eyed, smiling, dark and curly-haired woman with educated, discrete, introverted and respectful personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the overvaluation of one over the other ends up compromising the education in line with the social changes (16) . It is believed, therefore, that this contextualized articulation between teaching and service facilitates learning and leads the student to a reflective practice based on a realistic experience in the different environments of the health services (17)(18) . As far as Professor Mary Anne Small is concerned, her former students presented some features that made it possible to project the image of a tall, wide-eyed, smiling, dark and curly-haired woman with educated, discrete, introverted and respectful personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff expressed confidence that students were able to reduce this burden depending on their preparedness, attitude, and willingness to participate in the patient care experience. 18,19 "Sometimes, if students are hardworking and quick on the uptake, they quickly 'get' the task at hand -that makes things easier. But, if there are students who don't pick things up quickly, then it gets a bit more complicated, for example, if we are teaching them [students] at the same time as treating patients, and they need to be told more than once or twice, then this makes things more difficult for us" (Female nurse, 26, degree in Nursing).…”
Section: Original Articlementioning
confidence: 99%
“…20,21 However, nurse's negative attitudes towards students in terms of providing poor guidance and support can cause students to become frustrated; this can lead to some students under-participating in their placement. 19,21 Nursing student's view of their own role within the mentoring process tends to focus very much on their position as students on clinical placement. However, in practice, they frequently admitted feeling as though they are treated as extra helpers by the medical staff, and, as such, are often called upon to carry out tasks unrelated to their medical studies.…”
Section: "They Don't Get Involved In the Clinical Work… The Passive Omentioning
confidence: 99%
“…Various stressors have an impact on staff nurses including attitudes and motivation of the student, increase in workload, length of experience as a nurse, and workforce shortages. [4] Some studies found that there were both positive and negative aspects of nursing students' con-tributions to clinical practice. Registered nurses mentioned enhancement of their professional development as a positive attribute and increased demands on time and workload as a negative consequence.…”
Section: Introductionmentioning
confidence: 99%